PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN INFRASTRUKTUR RUAS ANJUNGAN KE BATAS SERAWAK - Odir Haituah; Yetrie Ludang; Stephanus Alexander (Bajang Institute, 2022)
This study aims to determine the perception of the community around the area on the development of road infrastructure from the Anjungan to the Sarawak border and to determine the impact of development on the economy of the surrounding community. The research approach used is a descriptive quantitative approach with data collection techniques using questionnaires and documentary studies. The results of the study show that the public has a positive perception of the existence of Road Infrastructure development from the Anjungan to the Sarawak boundary. Positive perceptions are also shown from the aspect of information and transparency as well as changes in activities, while for the environmental impact aspect, people tend to have negative perceptions. There is a relationship between aspects of perception of information and transparency with the level of knowledge